Career Counseling Urgency: Career Planning Capability of Substance Users in the Rehabilitation Process - Sutoyo, Anwar; Supriyanto, Agus; Arikunto, Suharsimi; Wibowo, Mungin Eddy; Mulawarman, Mulawarman; Purwadi, Purwadi; Saputra, Wahyu Nanda Eka; Hendiani, Nurlita (Counsellia: Jurnal Bimbingan dan Konseling, 2022)
Individuals with substance abuse disorders (S-AD) are also human beings who need self-development and future careers. The career development of individuals with GPZ hasn’t been fully considered in planning drug rehabilitation programs, although overall, the rehabilitation program has been excellent. Measurement of career planning ability needs to be measured by the condition of individuals with GPZ. The purpose of this study was to analyse the career planning abilities of individuals with GPZ undergoing drug rehabilitation and the urgency of career counselling. Mix-method research with explanatory sequential design begins with quantitative data and then integrates qualitative data. The data on career planning ability variables were collected on research subjects in individuals with GPZ. Quantitative data were collected through a career planning ability questionnaire with 32 questions, then qualitative data through interviews with one individual, all taken by random sampling—the average career planning ability of individuals with low GPZ. Counsellors should be able to develop ten career planning skills on how to learn information, career discussions with adults, training related to education, knowledge of working conditions, discussion of career challenges, planning work after rehabilitation programs, managing leisure time, developing self-confidence during rehabilitation, as well as the state of oneself when working without illegal drugs. Although career planning skills are low, addiction counsellors have a role in their development, with ten abilities discovered through career counselling. Career counselling as an addiction counsellor attempts to help individuals with GPZ develop their potential.